Paradigma Gender dan Model Gerakan 'Aisyiyah Sulawesi Selatan pada Masa Orde Baru - Hadisaputra Hadisaputra (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
There are still very few studies on the Aisyiyah Movement in South Sulawesi. Aisyiyah's contribution to South Sulawesi's development has never been publicized. This paper analyzes the 'Aisyiyah movement's role in advancing the social lives of South Sulawesi women during the New Order Era. The historical approach is applied in four stages in this study: heuristics (source collecting), verification (source critique), interpretation, and historiography (historical writing). The research findings indicate that Aisyiyah's gender paradigm encourages its members to engage in activities other than household work. Women are encouraged to take an active role in society and preach in the same way that men do. This shift in perspective began to be implemented in order to give women with equal rights, duties, and positions. 'Aisyiyah never took a frontal position with the government during the New Order. To continue her da'wah agenda, mainly in the areas of education, social and health, Aisyiyah prefers to adopt a conformist-adaptive strategy.